A model of outcome-based education (OBE) for engineering education / Asmidar Alias and Norshariza Mohamad Bhkari - Alias, Asmidar; Mohamad Bhkari, Norshariza (Universiti Teknologi MARA Cawangan Pahang, 2007)
Outcome-Based Education (OBE) is an educational system which has been enforced on all engineering programmes. The driving force for this change is the current higher learning education development, which is an accreditation regulatory in the Malaysian Qualification Agency (MQA) Act. Shifting towards this new practice, the concept and delivery of OBE should first be recognised by any Institution of Higher Learning (IHL) provider for accreditation purposes. This paper focuses on the driving force and an implementation model of OBE practices in the Faculty of Civil Engineering (FCE) UiTM Pahang.